Using a Delphi survey to gain an international consensus on the challenges of conducting trials with adults with intellectual disabilities. (April 2020) - Mulhall, Peter; Taggart, Laurence; Coates, Vivien; McAloon, Toni
Background/aims: People with intellectual disability experience higher rates of multi-morbidity and health inequalities, they are frequently prescribed medications and more likely to have an avoidable or premature death. There is a recognised lack of randomised controlled trials, and subsequently a lack of evidence base, for many of the interventions and treatments provided to people with intellectual disabilities. Very few disability-specific trials are conducted, and people with intellectual, and other cognitive, disabilities are routinely excluded from mainstream trials. There is an urgent need to facilitate more disability-specific trials or to encourage mainstream trialists to include people with disabilities in their studies. Obtaining a thorough understanding of the challenges inherent in these trials, and sharing this knowledge within the research community, may contribute significantly towards addressing this need. The aim of this study was to explore the practical and methodological challenges to conducting trials with adults with intellectual disabilities and to reach a consensus regarding which are the most important challenges for researchers for inclusion in a resource toolkit. Methods: A three-round modified Delphi survey was conducted with a panel of international trials researchers within the intellectual disability field. Items were assessed in terms of the consensus level and stability of responses. Results: A total of 64 challenges and barriers were agreed upon, across all aspects of the trial pathway, from planning through to reporting. Some challenges and barriers had been noted in the literature previously, but many previously uncited barriers (both systemic and attitudinal) were identified. Conclusion: This is the first international survey exploring the experiences of researchers conducting randomised controlled trials with adults with intellectual disabilities. Many of the barriers and challenges reported can be overcome with creativity and some additional resources. Other challenges, including attitudes towards conducting trials with disabled populations, maybe harder to overcome. These findings have implications for conducting trials with other populations with cognitive or communication difficulties. Implications for disability researchers, funding bodies and ethical review panels are discussed.